Efeitos do programa PEERS e análise da assimetria cerebral de jovens brasileiros com autismo e/ou deficiência intelectual - Mori, Fernanda Yumi Ribeiro (2024)
During adolescence and early adulthood, social interactions intensify due to exposure to new environments, stimuli and the building of more lasting relationships, leading to greater autonomy and social interaction. In the area of social skills (SS), making friends involves a class of behaviors that can be taught and evaluated in educational interventions. The study aimed to evaluate the effect of PEERS (Program for the Education and Enrichment of Relational Skills) with young people with autism and/or intellectual disability (ID), in the context of the São Paulo metropolitan region, using neurophysiological measures (cerebral asymmetry) analyzed by electroencephalogram (EEG) and behavioral measures (for example, asking and answering questions on and off topic, spontaneous behavior on and off topic, among others). The program was applied to six young people (one with autism, three with autism and ID, two with ID) in 14 sessions. Behavioral measures were analyzed during the intervention, while brain symmetry was analyzed as a function of pre-test, intermediate measure (after the 7th week) and post-test. The results showed that the young people exhibited more social skills during the intermediate sessions and the EEG results showed greater activation in the left hemisphere than in the right in the intermediate measurements, as expected by the study. The program needs to be improved, especially in terms of intervention time and ensuring family involvement.